Menonton Kartun Efektif Menurunkan Nyeri Pemasangan Infus dan Venipuncture pada Anak - Elfrida Silalahi; Nani Nurhaeni; Imami Nur Rachmawati (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of non-pharmacological therapy of watching cartoons in treating children's pain during infusion and venipuncture. The method used is a systematic review using guidelines from the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). The research results showed ten articles selected after selection and quality assessment using guidance from the JBI critical appraisal tool. Watching videos effectively reduces pain in children during infusion and venipuncture with p<0.05. In conclusion, the videos watched by children are adjusted to the child's preferences and age. Nurses are expected to be able to use non-pharmacological pain management strategies to provide the best care for pediatric patients. Keywords: Watching Cartoons, Pain, Pediatrics, Venipuncture